LITERATURE REVIEW: METRIC SOFTWARE DALAM PENGEMBANGAN EVALUASI SOFTWARE - Novriansyah, Ramadhan; Fitria, Riska; Putra, ZalfaRafi; Sugiarti, Yuni (Universitas Muhammadiyah Bangka Belitung, 2024)
The use of metrics in software as an analysis method is considered quite difficult in application development. Many companies use this method. The research we conducted aimed to analyze software quality metrics and determine the absence of a common standard for selecting metrics in software testing systems. Our research method involved analyzing various software quality metrics to understand the diversity in metric selection practices among developers. The results of this study reveal that developers must devise their own methods for evaluating software quality given the specific characteristics of the industry in which the software will be used